The The Effect of Firm Size, Firm Age, and Profitability on Firm Value in Food and Beverages Companies Listed On The Indonesia Stock Exchange For The Period 2024 - R. Enough Bhaktiar; Sistya Arini (Jurnal Akuntansi Bisnis dan Ekonomi, 2025)
This study aims to analyze the impact of firm size, firm age, and profitability on firm value in the Food and Beverages company listed on the Indonesia Stock Exchange (IDX) during the 2024 period. The method used is quantitative using secondary data from the company’s financial statements. The population in this study was a Food and Beverages company listed on the Indonesia Stock Exchange. The sampling technique used is the simple random sampling method and 79 samples are obtained. The analysis technique applied is multiple linear regression using the Statistical Package for Social Science (SPSS) version 23. The results show that the firm size, firm age and profitability have a significant effect on the value of company company Food and Beverages. The firm size has a positive positive effect on the firm’s value, the company’s age negatively has a significant negative effect on the company’s value, while profitability has a significant positive effect on the company’s value.